PENGARUH KEMAMPUAN MENGGUNAKAN TEKNOLOGI KOMUNIKASI, SOSIALISASI MEDIA PEMBELAJARAN ONLINE, DUKUNGAN KELUARGA DAN PENGAJAR TERHADAP KEAKTIFAN MAHASISWA DI MASA PANDEMI COVID-19 - Syamsul Bakhri; Teddy Dyatmika; M. Rikzam Kamal (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2020)
Utilization of communication technology when used as a complement to direct face-to-face learning has a very positive impact, making it easier for students and teachers to maximize the learning process. But during the Covid-19 Pandemic the use of communication technology in the whole learning process caused various problems and obstacles. Research is needed on how much influence the ability of students to operate communication technology, how the socialization of learning through communication technology at the time of the Covid-19 epidemic and the support of families and teachers on active learning in the Covid-19 pendemi period. This research uses explanative quantitative methods which are analyzed using Rogers Innovation Diffusion theory. Data analysis using Linear Regression Test. The results of the study showed a significant influence of the three independent variables, namely the ability to use communication technology (X1), online learning media socialization (X2) and family and teacher support (X3) together on student activity (Y). The magnitude of the effect is 54.8% and is positive. This means that the higher the value of the three independent variables, the better the student's activeness in learning. In this study also there is still 45.2% the influence of other variables on student activity during the Covid-19 Pandemic.